INFLUENCE OF IDEOLOGICAL AND POLITICAL FACTORS ON COLLEGE STUDENT’S ACADEMIC PERFORMANCE - Ma Zhong Qiu, Cheng Yang An (Chelonian Research Foundation, 2023)
Student confidence, drive, and persistence in school are all significantly impacted by academic achievement. There may be intolerable levels of turnover, decreased degree output, and higher expense of education if students do not perform adequately in their coursework (Emerson et al., 2023). This also makes it harder for students to enroll in postsecondary institutions and earn advanced degrees. Therefore, teachers have always been interested in their pupils' scholastic progress. Researchers and teachers have been interested in what factors lead to success in school for quite some time. Education is one of the key factors that promotes national unity since learners from divergent backgrounds converge and interact despite of their backgrounds. Believes, values, customs and political inclinations individuals have forms a platform for ideological and political factors (Mamanovich, 2021). However, some believes tend to me more influential than others causing division among students thus causing poor academic performance as students may feel inferior based on their believes. On the same context, ideological and political factors forms groups as results of a specific identity among students thus motivating them to operate as a team (Guay & Johnston, 2022). This implies that within learning institutions, there are numerous groups, which have same social values, political affiliations and ideological factors. There is a close connection between the national politics of a country and college politics. In some scenarios, the politics among college students are linked with politicians who fund students in their campaigns. Therefore, it is impossible to discuss the ideological and political differences among college students in isolation of national politics. Students may become divided not only between different ideologies but also within the same ideology, which can result in conflict, discrimination, prejudice, suppression, competition, unfairness, and even war (Clark & Winegard, 2020). Social media usage is most used among college students. However, the ideological differences may arise based on the attitude, believes and perceptions individuals or groups have towards a given context or celebrity. Studies have indicated that academic performance among students is influenced by learning styles, economic backgrounds, learning environments, teacher factors, genetics and dietary factors. However, few studies have addressed how ideological and political factors influence student’s performance in the college level. The following literature depicts ideological and political factors influencing academic performance.